Marketing Discourse Analysis in Kurdish Social Media During Covid-19: Express Delivery Companies for Example - Taha, Hiwa J.; Sherwani , Prof. Dr. Kawa A.; Mstaffa , Asst. Prof .Dr. Abdulkhalq E. (Mitanni Journal of Humanitarian Sciences, 2023)
Abstract: This study entitles “Marketing Discourse of Kurdish Social Media During Covid-19”: . It deals with the marketing discourse of delivery companies on social media during the spread of Covid-19 in Iraqi Kurdistan Region. It aims at identifying the relationship between marketing discourse of the delivery companies and social media tools used at that period. The study uses discourse analysis and content analysis. It also uses survey as a tool to collect data from two delivery companies, namely ‘Talabat’ and ‘Lezzoo’. The study incorporates all delivery companies in the region, but the sample of the study is the two mentioned companies, that have their offices in Iraqi Kurdistan Region. The study concludes that the most important topics used in the discourse of marketing on Kurdish social media by the delivery companies, on Facebook and Instagram, during covid-19, were introducing the companies’ services and cultivating the audience. The two companies focus on the discourse of emotion to get the attention of the audience in order to get their trust and confidence.